Applicability of theory of planned behavior and protection motivation theory in predicting intention to purchase health insurance / Nor Azmaniza Azizam … [et al.] - Azizam, Nor Azmaniza; Dzulkipli, Mohd Redhuan; Shamimi, Nor Intan; Maon, Siti Noorsuriani; John, Disera; Belawing, Jennifer; Jawa, Judith; Yahaya, Nuraqirah (Universiti Teknologi Mara Selangor, 2020)
In the era of increasing healthcare cost, private medical and health insurance ownership substantially reduces out of pocket expenses for medical care. The main objective of this paper is to apply theory of planned behavior and (TPB) model and protection motivation theory (PMT) in predicting intention to purchase health and medical insurance among graduating students. A cross-sectional survey was performed for data collection. A total of 443 questionnaires were completed and valid for data analysis purposes. Findings showed that there was statistically significant correlation between attitudes and subjective norm with the intention to purchase medical insurance. Severity, vulnerability and self-efficacy correlate negatively, while response efficacy demonstrates a positive correlation. Despite of the negative perception over private insurance, it significantly reduces out of pocket expenditures for medical care. Thus, there is a need of a further study examining the factors affecting the demand and individual’s decision purchasing private insurance in Malaysia